The international EAACI/GA²LEN/EuroGuiDerm/APAAACI guideline for the definition, classification, diagnosis, and management of urticaria. Issue 3 (20th October 2021) - Zuberbier, Torsten; Abdul Latiff, Amir Hamzah; Abuzakouk, Mohamed; Aquilina, Susan; Asero, Riccardo; Baker, Diane; Ballmer‐Weber, Barbara; Bangert, Christine; Ben‐Shoshan, Moshe; Bernstein, Jonathan A.; Bindslev‐Jensen, Carsten; Brockow, Knut; et al.
Abstract: This update and revision of the international guideline for urticaria was developed following the methods recommended by Cochrane and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) working group. It is a joint initiative of the Dermatology Section of the European Academy of Allergology and Clinical Immunology (EAACI), the Global Allergy and Asthma European Network (GA²LEN) and its Urticaria and Angioedema Centers of Reference and Excellence (UCAREs and ACAREs), the European Dermatology Forum (EDF; EuroGuiDerm), and the Asia Pacific Association of Allergy, Asthma and Clinical Immunology with the participation of 64 delegates of 50 national and international societies and from 31 countries. The consensus conference was held on 3 December 2020. This guideline was acknowledged and accepted by the European Union of Medical Specialists (UEMS). Urticaria is a frequent, mast cell–driven disease that presents with wheals, angioedema, or both. The lifetime prevalence for acute urticaria is approximately 20%. Chronic spontaneous or inducible urticaria is disabling, impairs quality of life, and affects performance at work and school. This updated version of the international guideline for urticaria covers the definition and classification of urticaria and outlines expert‐guided and evidence‐based diagnostic and therapeutic approaches for the different subtypes of urticaria.